Autonomous robot navigation for automotive assembly task: an industry use-case - Sobreira, Héber (2020)
Automobile industry faces one of the most flexible productivity caused by the number of customized models variants due to the buyers needs. This fact requires the production system to introduce flexible, adaptable and cooperative with humans solutions. In the present work, a panel that should be mounted inside a van is addressed. For that purpose, a mobile manipulator is suggested that could share the same space with workers helping each other. This paper presents the navigation system for the robot that enters the van from the rear door after a ramp, operates and exits. The localization system is based on 3DOF methodologies that allow the robot to operate autonomously. Real tests scenarios prove the precision and repeatability of the navigation system outside, inside and during the ramp access of the van.